Transient free convection in parallelogrammic cavities applied to the thermoregulation of avionics. (1st March 2010) - Bairi, A.; Pernia, E. Zarco; Laraqi, N.; Garcia De Maria, J.M.; Gutierrez, F.; Campo, A.; Chanetz, B.; Oztop, H.F.
This work addresses momentum and heat transfer phenomena that take place in closed cavities filled with air. The cavities are formed by two vertical active walls, one hot consisting of bands that are alternately insulated and heated at temperature Th and other cold, isothermal at Tc. The closing upper and lower passive walls can be tilted an angle αeither above or below the horizontal plane. When α is positive (hot wall below the level of the cold one), the air movement is favoured while the opposite occurs for negative angles. These cavities are thus either transferring or insulating, which confers them the quality of a so-called convective diode. Such geometry is applied in this work to the thermoregulation of the on-board aviation electronics. The flows corresponding to different angles and temperature differences ΔT = Th – Tc are examined both numerically and experimentally. We consider in particular the transient transport phenomena which occur at the very beginning, a critical stage in the operation of the on-board materials.